GLOBAL REFLECTION ON INDIA’S FIGHT AGAINST CORONA - Sanghamitra Dash (Journal of Biomedical and Pharmaceutical Research, 2020)
India’s relative success in fighting corona pandemic makes the concerned observers inquisitive of global strategic canvas, positional strengths and implementation challenges that have emerged for India. An attempt to respond to the threefold query is made in this brief analysis. Keywords: India, Corona, Public Health, Ayurveda, Ancient Therapy, Globalisation